A Phonologically Based Intervention for School-Age Children With Language Impairment: Implications for Reading Achievement. (December 2013) - Ritter, Michaela J.; Park, Jungjun; Saxon, Terrill F.; Colson, Karen A.
This study was conducted utilizing a quasi-experimental pre- and postgroup design to examine the effects of a phonologically based intervention aimed to improve phonological awareness (PA) and reading abilities in school-age children with language impairment (LI) in Grades 1 through 3. The intervention included instruction in PA and sound-symbol correspondence. Sixty-four school-age children with LI (Grades 1-3) were assigned to either an experimental ( n = 34) or a control group ( n = 30). Eleven kindergarten-age children with LI were then included as a comparison grade group to investigate whether the magnitude of treatment effect changed across grade level in the experimental group (K-3). Participants in the experimental group (Grades 1-3) made significantly greater gains in PA and reading (e.g., decoding and text comprehension) than the control group. Similar gains were observed across the varying grade levels (K-3). These results suggest that, despite being at risk of reading failure, school-age children with LI in Grades 1 through 3 have the potential to make accelerated gains in their reading development and in the PA skills that are essential to successful literacy acquisition.